Soft polar molecular layers adsorbed on charged nanowire - Lykah, V.A.; Syrkin, E.S. (Condensed Matter Physics, 2004)
A selfconsistent theoretical approach is developed for describing an uncompensated charge carrier inside a perfect semiconductor quantum wire covered with a soft molecular layer. Deformation of the molecular layer under inhomogeneous carrier electric field is described in the model of liquid crystal with intrinsic electric dipole. The longitudinal quantization of a charge carrier is reduced to the spectral problem for nonlinear Schrodinger equation which is solved in terms of elliptic functions. The features of behavior of the system are as follows: the higher is the interaction, the higher is the nonlinearity; the lowest quantum levels experience the highest nonlinearity; the effect should be more pronounced for heavier holes. Under the increase of interaction the carrier is localized. The occurrence of localized states could be responsible for the experimentally observed decrease of conductivity in nanowires.